Obesity in pregnancy stimulates macrophage accumulation and inflammation in the placenta - Challier, JC (Placenta, 2008)
Obesity and pregnancy are associated with a combination of insulin resistance and inflammatory changes which exacerbate in combination. Based on the similarity between the inflammatory transcriptomes of adipose tissue and placenta, we hypothesized that the placenta develops exaggerated inflammation in response to obesity. The aim of this study was to characterize placental inflammatory mediators and macrophage accumulation in relation to peripheral inflammation in obesity. Placental macrophages and maternal peripheral mononuclear cells from 20 obese and 15 lean women were functionally and phenotypically characterized using immunohistochemistry, flow cytometry and expression for macrophage markers and inflammatory cytokines. The number of resident CD68+ and CD14+ cells was increased 2-3 fold in placenta of obese as compared to lean women. The enhanced macrophage population was characterized by a marked phenotypic heterogeneity with complex subsets of CD14+, CD68+ and CD11b+ cells and by an increased expression of the pro-inflammatory mediators IL-1, TNF-alpha, IL-6. Placental inflammation was associated with an activation of peripheral blood mononuclear cells with high amount of CD14, TNF-alpha, IL-6 and the chemokine receptors CCR2 and IL8-R in maternal but not fetal circulation. Additionally, plasma CRP and IL-6 concentrations were higher in obese compared to lean women. In conclusion, the chronic inflammation state of pre-gravid obesity is extending to in utero life with accumulation of an heterogeneous macrophage population and proinflammatory mediators in the placenta. The resulting inflammatory milieu in which the fetus develops may have critical consequences for short and long term programming of obesity.